2016
DOI: 10.1016/j.math.2016.05.157
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between lumbar dysfunction and fat infiltration in lumbar multifidus muscles in patients with low back pain

Abstract: Background: Lumbar multifidus muscles (LMM) are important for spinal motion and stability. Low back pain (LBP) is often associated with fat infiltration in LMM. An increasing fat infiltration of LMM may lead to lumbar dysfunction. The purpose of this study was to investigate whether there is a correlation between the severity of lumbar dysfunction and the severity of fat infiltration of LMM. Methods: In a cross-sectional study, 42 patients with acute or chronic LBP were recruited. Their MRI findings were visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 6 publications
(6 reference statements)
5
30
0
Order By: Relevance
“…Some studies assessed LBP with fatty degeneration of the multifidus or both the multifidus and erector spinae, and some of them support the association of LBP with fatty degeneration [13][14][15][19][20][21]. In our study, we also found that muscle fatty degeneration increased with LBP.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Some studies assessed LBP with fatty degeneration of the multifidus or both the multifidus and erector spinae, and some of them support the association of LBP with fatty degeneration [13][14][15][19][20][21]. In our study, we also found that muscle fatty degeneration increased with LBP.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies have shown that fat deposition in paravertebral muscles increases with the aging process [14,18,22,24]. In our study, similarly, in both case and control groups patients aged > 40 years were observed to have more fat deposition compared to patients aged < 40 years.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Although LBP is often considered as a complex or multifactorial disorder with many potential causative factors, in majority of cases (90%), the cause of the pain is unknown which is commonly referred to as nonspecific LBP (Balagué et al, 2012). However, there are different interpretations of the underlying mechanisms of pain even when specified radiological diagnoses are established (Hildebrandt et al, 2017). One mechanism that has been linked with LBP is the altered stability and motor control of specific muscles of the trunk.…”
Section: Introductionmentioning
confidence: 99%